Relationship of Citizenship Education, Pancasila and Religious Character - Choirul Mahfud; Niken Prasetyawati; Ni Wayan Suarmini; Dyah A.Y Agustin; Enie Hendrajati; Didik Supriyanto (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2020)
Recently, Pancasila has again become a trending topic in the national issue in Indonesia. Studies on the relationship between civic education, Pancasila, and religious character are still rarely carried out. However, it is realized that it is essential to support an intelligent society's realization and love harmony and peace for the nation's progress. This research is a qualitative study with a descriptive-analytical approach using a literature-based documentary method. This research's general objective is to understand the relationship between civic education, Pancasila, and religious character. This study's findings are that the relationship between Pancasila, civic education, and religious character is very close and needs to be kept in mind. Many people still agree that Pancasila does not need changes, amendments, and the like. More than that, Pancasila's practice in the world of education and the nation's life, religion, and state.